NON-REFOULEMENT AND ACCESS TO ASYLUM - Kakosimou, Vasiliki (PEOPLE: International Journal of Social Sciences, 2017)
Contemporary border management situations may trigger refoulement, whereas international refugee law and human rights law prohibit the return to a risk of persecution, torture, inhuman or degrading treatment or punishment. The applicability of non-refoulement, once a State exercises effective control over an individual by his officials, is contravened by international deterrence strategies. Practices of non-entrée are measures taken by States to deal with mass refugee influxes, but breach the fundamental prohibition against refoulement and result in limiting access to asylum. In the EU, non-refoulement and the prohibition of collective expulsions are tightly linked with for safeguarding access to the asylum procedure. The principle of non-refoulement also comes to play in the event of a transfer in the framework of the Dublin Regulation and upon a return after a negative and final decision on the application or as a possible consequence of the ending of the protection. Apart from a few and specific exceptions, the principle of non-refoulement has an absolute nature that ensures the right to asylum, even in cases of emergency for a Member State.